2019
DOI: 10.1177/2382120519840350
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Provider Critical Care Boot Camp: A Simulation-Based Curriculum

Abstract: The demand for advanced practice providers (APPs) is increasing across the United States to meet necessary provider staffing requirements including in intensive care settings. Currently, participation in formal postgraduate training programs, or residencies, for APPs is not required for clinical practice, such that most of the APPs immediately enter into the workforce following completion of their initial graduate-level training. Consequently, this results in a supervised training period until APPs develop the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Second, a standardized onboarding process that is focused on new hire knowledge and skills and tailored to their specific needs and clinical contexts helps create a supportive APN/PA culture. 16 , 17 , 18 , 19 UCM has created a hospital‐level onboarding committee. Within HM, this includes a required quality improvement project which exposes new hires to the importance of professional development and systems‐based practice.…”
Section: Building An Apn/pa Culturementioning
confidence: 99%
“…Second, a standardized onboarding process that is focused on new hire knowledge and skills and tailored to their specific needs and clinical contexts helps create a supportive APN/PA culture. 16 , 17 , 18 , 19 UCM has created a hospital‐level onboarding committee. Within HM, this includes a required quality improvement project which exposes new hires to the importance of professional development and systems‐based practice.…”
Section: Building An Apn/pa Culturementioning
confidence: 99%
“…Didactic components include published syllabi; program goals, expectations, and rules of conduct; traditional topical lectures by specialists; modular e-learning assignments; faculty-approved podcasts; textbook readings; and inhouse medical lectures pertinent to the competencies. Additional training is obtained using simulation laboratories in conjunction with written clinical scenarios 24…”
Section: Overview Of Trainingmentioning
confidence: 99%
“…Future research in the area of additional training should look at cost-effective methods of imparting critical knowledge, skills, and abilities to the complete healthcare delivery team. 20,24,28 Greater standardization of CPGT program recordkeeping is still needed, as is support for research into the longitudinal outcomes associated with training. 1 Institutional retention rates, professional satisfaction, and the effects of dedicated learning time on PA clinical confi dence would be useful data for administrators and CPGT program directors to prove the advantages and challenges of clinical training in an era of close budget scrutiny.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Multiple studies have demonstrated that simulation-based education improves APP confidence and skills ( 11 14 ). However, traditional simulation-based skill interventions do not hold participants to high or uniform standards ( 15 17 ) and are not often used to train participants to a competency standard.…”
mentioning
confidence: 99%